Language Learning and Teaching in Digital Environment - Lie, Anita; Gozali, Imelda; Wardhono, Agus (Journal of NELTA, 2023)
The impetus for this conceptual article was derived from the panel discussion on “Language Learning and Teaching in Digital Environment” in the 27th NELTA International Conference 2023 and the authors’ reflections on their experiences as teachers and teacher educators in Indonesia, particularly after the unprecedented lock-down. The recent school closure has off ered lessons learned on the need for digital pedagogy and led to the new awareness of the challenges and opportunities in the inevitable digital environment. This article discusses some of the major contextual changes and the future directions of digital pedagogy for language learning.